Pengaruh Literasi Keuangan, Sistem Informasi Akuntansi dan Penggunaan Sosial Media Terhadap Efektifitas Kinerja UMKM - Hanifah Aprilia; Sulastiningsih (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This research aims to analyze the influence of financial literacy, accounting information systems and social media on the effectiveness of MSME performance. Improving the effectiveness of MSME performance is very important because MSMEs have a large contribution to the Indonesian economy, one of which is Wonosobo Regency. Financial literacy, accounting information systems and the use of social media are predicted to be factors that influence increasing the effectiveness of MSME performance. The sample in this research was 100 MSMEs in Wonosobo Regency, Central Java. Research data was obtained by distributing questionnaires and using the purposive sampling method. The results of this research state that financial literacy does not have a positive effect on the effectiveness of MSME performance, while accounting information systems and social media have a positive effect on the effectiveness of MSME performance. Financial literacy, accounting information systems and social media can help MSMEs innovate, optimize the use of financial resources and improve performance.